Potential Biomarkers for Diagnosing Major Depressive Disorder Patients with Suicidal Ideation - Bai S (Dove Medical Press, 2021)
Shunjie Bai,1 Liang Fang,2,3 Jing Xie,4 Huili Bai,1 Wei Wang,5 Jian-jun Chen6 1Department of Laboratory Medicine, The First Affiliated Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 2Department of Neurology, Yongchuan Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 3Chongqing Key Laboratory of Cerebral Vascular Disease Research, Yongchuan Hospital of Chongqing Medical University, Chongqing, People’s Republic of China; 4Department of Endocrinology and Nephrology, The Fourth People’s Hospital of Chongqing, Chongqing, People’s Republic of China; 5Department of Neurology, The Affiliated Hospital of Guizhou Medical University, Guiyang, People’s Republic of China; 6Institute of Life Sciences, Chongqing Medical University, Chongqing, People’s Republic of ChinaCorrespondence: Jian-jun Chen, Email chenjianjun@cqmu.edu.cnBackground: Major depressive disorder (MDD) and suicide are two major health problems, but there are still no objective methods to diagnose MDD or suicidal ideation (SI). This study was conducted to identify potential biomarkers for diagnosing MDD patients with SI.Methods: First-episode drug-naïve MDD patients with SI and demographics-matched healthy controls (HCs) were recruited. First-episode drug-naïve MDD patients without SI were also included. The serum lipids, C-reactive protein (CRP), transferring (TRSF), homocysteine (HCY) and alpha 1-antitrypsin (AAT) in serum were detected. The univariate and multivariate statistical analyses were used to identify and validate the potential biomarkers.Results: The 86 HCs, 53 MDD patients with SI and 20 MDD patients without SI were included in this study. Four potential biomarkers were identified: AAT, TRSF, high-density lipoprotein cholesterol (HDLC), and apolipoprotein A1 (APOA1). After one month treatment, the levels of AAT and APOA1 were significantly improved. The panel consisting of these potential biomarkers had an excellent diagnostic performance, yielding an area under the ROC curve (AUC) of 0.994 and 0.990 in the training and testing set, respectively. Moreover, this panel could effectively distinguish MDD patients with SI from MDD patients without SI (AUC=0.928).Conclusion: These results showed that these potential biomarkers could facilitate the development of an objective method for diagnosing MDD patients with SI, and the decreased AAT levels in MDD patients might lead to the appearance of SI by resulting in the elevated inflammation.Keywords: major depressive disorder, suicidal ideation, biomarkers